Feasibility of Malaysian International Shipping Corporation to set up a ship management company / Azman Osman. - Osman, Azman (1991)
Ship Management Company has already become common in western countries. Ship Management Company is a third party who manages ships on behalf of ship-owners. Ship management services has already spread over this region especially in countries like Hong Kong and Singapore. The purpose of this research is to study the demand and potential market for the ship management services in Malaysia. The study is also to analyse the performance of MISC in managing its own fleet of vessels. Beside that the research will also overview the scene of Malaysian shipping industry as a whole. Another aspect of this" study is to find a suitable location to set up a ship management company. The study will be limited to the target market. Nowadays shipping industry has a very good prospect due to the boom in oil exploration activities which requires more tankers and support and supply vessels. The increase in production of Malaysian LUG created the needs for expertise in ship management. MISC with its vast experience in managing its LNG tankers makes it suitable for them to set up a subsidiary company of ship management. Hopefully the growth in county's economic, increase production in Malaysian LNG and the boom in oil exploration activities will attract investors/entrepreneurs involvement in shipping industry Thus, due to lack of shipping knowledge of these investors will enhance the need of ship management company.